“EFL Adult Learners’ Attitudes towards Learning Speaking” - Khater, Hanane (My University, 2017)
The present work aims at exploring EFL second year students attitude towards learning speaking skill and causes that might have hindered their learning such as psychological problems, linguistic difficulties and the use of mother tongue. The objective of this study was to investigate the causes that may have influenced EFL speaking proficiency for students perspectives. The hypothesis of this dissertation is that attitude plays an important role in learning English as a foreign language. Thus, if students have a positive attitude towards learning EFL speaking skill; they may achieve higher results and become proficient speakers. If not, their speaking skill may become bad. A case study research was conducted in Abd Elhamid Ibn Badis University of Mostaganem relying on (questionnaire )for second year learners. Results of the quantitative analysis show that the attitude towards EFL speaking and using the language is extremely positive. The data also revealed that most of the students had negative feelings or fear regarding classroom instructions and teachers strategies in their learning experience. Also, the results revealed that students improve their speaking skill through self-confidence, motivation, discussions in conversations. On the otherhand, teachers encourage their students by using different strategies. At the end, some recommendations were presented to enhance the skill of speaking among university students.
case of second year LMD students at the University of mostaganem
Keywords: Speech learning; Psychological problems; Language difficulties and the use of the mother tongue